Our Pandemic Year: On the Comics Scholarship to Come. Issue 1 (9th December 2020) - Dunley, Kathleen; Priego, Ernesto; Wilkins, Peter
Abstract : This editorial article reflects on the past, present and future of The Comics Grid: Journal of Comics Scholarship . It discusses the challenges overcome so far, and discusses the tenth volume of the journal, corresponding to 2020, "our pandemic year". The article presents the authors' vision for the type of comics scholarship they would like to see in future volumes of the journal, calling for greater diversity and inclusion and for work which is 'media-specific' in at least three ways: firstly because the field's focus is comics, in all their multifaceted diversity, complexity and vibrancy; secondly because the study of comics, like many of the studied comics themselves, mostly exist and take place today somewhere in the spectrum of digital environments, and thirdly because comics studies as a field operates within academic institutions and cultures, and therefore plays a role within established hierarchies of knowledge production.